Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Semi-synthesis of deoxyartemisinin - Bhattacharya, Asish K.; Pathak, Ashish K.; Sharma, Ram P. (Mendeleev Communications, 2007)
The reaction of artemisinin with aluminium-nickel chloride hexahydrate in THF or nickel boride in MeOH furnishes deoxyartemisinin in an excellent yield.

Amberlite-IR 120 catalyzed three-component synthesis of alpha-amino phosphonates in one-pot - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Tetrahedron Letters, 2008)
A simple, efficient, and environmentally benign method for a three-component reaction of an amine, an aldehyde or a ketone, and diethyl phosphite catalyzed by Amberlite-IR 120 resin has been developed to afford alpha-amino phosphonates in high yields and short reaction times under solvent-free reaction conditions. The major advantages of the present method are good yields, inexpensive, ecofriendly and reusable catalyst, mild and solvent-free reaction conditions and tolerance towards various functionalities present in the substrates. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; ion-exchange resin; multi-component reaction

Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions

SbCl(3) as a highly efficient catalyst for the acetylation of alcohols, phenols, and amines under solvent-free conditions - Bhattacharya, Asish K.; Diallo, Mamadou A.; Ganesh, Krishna N. (Synthetic Communications, 2008)
Antimony trichloride has been found to be an efficient and expedient catalyst for the acylation of alcohols, phenols, amines, and sugars with acetic anhydride in high yields and in a short reaction time under solvent-free conditions at room temperature. Also, racemization of chiral alcohols and epimerization of sugars were not observed in any of the substrates.
Keywords: acetic anhydride; acetylation; antimony trichloride; solvent-free conditions

Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes

Synthesis of the antibacterial benzoquinone primin and its water-soluble analogue, primin acid - Bhattacharya, Asish K.; Kaur, Tanpreet; Ganesh, Krishna N. (Synthesis-Stuttgart, 2010)
The biologically active natural product, primin and its water-soluble acid analogue, primin acid are prepared in 34% and 25% overall yields, respectively, from a common intermediate using a Grignard reaction and a Johnson-Claisen rearrangement as the key steps.
Keywords: 1; 4-benzoquinones; Antibacterial; Johnson-Claisen rearrangement; primin; primin acid

Design, synthesis and biological evaluation of peptidyl-vinylaminophosphonates as novel cysteine protease inhibitors - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Bioorganic & Medicinal Chemistry, 2011)
We report herein, design and synthesis of vinylaminophosphonates, a novel class of compounds as possible cysteine protease inhibitors. The synthesis of vinylaminophosphonates has been accomplished employing Tsuji-Trost reaction as a key step. The synthesized compounds were assayed against papain, a model cysteine protease and some of our synthesized compounds showed IC50 values in the range of 30-54 mu M thereby suggesting that these chemical entities thus could constitute an interesting template for the design of potential novel protease inhibitors. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cysteine; Inhibitor design; Protease inhibitors; synthesis; Tsuji-Trost reaction; Vinylaminophosphonates

Efficient synthesis of benzodiazepinyl phosphonates as clostripain inhibitors via FeCl3 catalyzed four-component reaction - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Raut, Dnyaneshwar S.; Mhaindarkar, Vaibhav P.; Khan, Mohammad Islam (Organic & Biomolecular Chemistry, 2011)
A novel one-pot route for the synthesis of benzodiazepinyl phosphonates (BDPs) has been achieved. FeCl3 efficiently catalyzed four-component condensation of diamines, acetone and phosphites in the presence of molecular sieves to furnish BDPs as novel chemical entities with good yield. The synthesized BDPs have shown significant protease inhibition activity against clostripain, a disease model for gas gangrene, suggesting that these novel chemical entities could be further explored as cysteine protease inhibitors.

Efficient synthesis of a hydroxyethylamine (HEA) isostere and its alpha-aminophosphonate and phosphoramidate derivatives as potential anti-HIV agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Pannecouque, Christophe; De Clercq, Eric (Chemmedchem, 2012)
HIV protease is a promising drug target for AIDS therapy, and several potent HIV-1 protease inhibitors have been reported to date. Although existing inhibitors exhibit high selectivity, they have also been associated with severe side effects and the possible emergence of therapeutic resistance. As HIV protease cleaves the peptide bond via a tetrahedral intermediate, various transition-state models such as hydroxyethylamine (HEA) have been designed. We therefore pursued an efficient synthesis of an HEA isostere; this was performed with a novel one-pot reductiontransiminationreduction reaction sequence as a key step. a-Aminophosphonate and phosphoramidate derivatives of the HEA isostere were designed and synthesized, and all of the synthesized derivatives were assayed for their anti-HIV activities against wild-type and mutant HIV strains. Phosphoramidate derivative 15?a was found to be the most active of all synthesized compounds against the IIIB and RES056 strains. As phosphonates are known to exhibit physiological stability, good cell permeability, and other promising pharmacokinetic characteristics, our newly synthesized compounds have the potential as alternatives to existing therapeutics and diagnostics.
Keywords: a-aminophosphonates; antiviral agents; hydroxyethylamine isosteres; phosphoramidates; synthesis

Antimycobacterial agent, (E)-phytol and lauric amide from the plant Lagascea mollis - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2013)
Chemical examination of aerial parts of the plant, Lagascea mollis has resulted in the isolation of two compounds, an acyclic diterpene alcohol which has been identified as (E)-phytol 1 and lauric amide 3. Their structures have been elucidated by spectral data and chemical transformations. This is the first report of isolation of both these compounds from this plant It is noteworthy that compound 1 has been found to be a potent antimycobacterial agent and thus, L. mollis could be exploited as an alternative source.
Keywords: amide; chemical transformation; diterpene; Lagascea mollis; structure elucidation

Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions

Efficient synthesis of 1,5-benzodiazepines catalyzed by bismuth nitrate - Bhattacharya, Asish K.; Dange, Santoshkumar S.; Polanki, Innaiah K.; Chand, Hemender R. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2014)
An efficient method has been developed for the synthesis of biologically active 1,5-benzodiazepines in one-pot by reacting o-phenylenediamine and ketones catalyzed by bismuth nitrate pentahydrate at room temperature or under microwave irradiation.
Keywords: 1; 5-benzodiazepines; bismuth nitrate pentahydrate; o-Phenylenediamine; synthetic methods

Chiral pool approach for the synthesis of functionalized amino acids: synthesis of antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (R)-lacosamide 1 has been achieved from N-Boc-N,O-isopropylidene-l-serinol 2 which could easily be obtained from natural l-serine. Our synthesis of 1 starting from 2 using chiral pool strategy resulted in 54% overall yield.

Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity

Direct glycosylation of unprotected and unactivated sugars using bismuth nitrate pentahydrate - Polanki, Innaiah K.; Kurma, Siva H.; Bhattacharya, Asish K. (Journal of Carbohydrate Chemistry, 2015)
Bi(NO3)(3), a low-cost, mild, and environmentally green catalyst, has been successfully utilized for Fischer glycosylation for the synthesis of alkyl/aryl glycopyranosides by reacting unprotected sugars, namely, D-glucose, L-rhamnose, D-galactose, D-arabinose, and N-acetyl-D-glucosamine with various alcohols in good to excellent yields. The glycosides were formed with high alpha-selectivity. Further, an expedient separation of alpha- and beta-glycosides using silver nitrate-impregnated silica gel flash liquid chromatography has been developed.
Keywords: Bismuth nitrate; carbohydrates; Fischer glycosylation; Flash chromatography; Separation

Synthesis of naturally occurring (+)-osmundalactone and 4-epi-(+)-osmundalactone from triacetyl-O-D-glucal - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (+)-osmundalactone 1 has been achieved starting from readily available triacetyl-O-D-glucal 6 employing Ferrier rearrangement and Jones oxidation as key steps. Also, synthesis of 4-epi-(+)-osmundalactone 2 was accomplished from the common key intermediate 9. The absolute stereochemistry of (+)-osmundalactone 1 and a precursor of 4-epi-(+)-osmundalactone 2 have been established by single crystal X-ray analysis. The overall yield of compound 1 and 2 from triacetyl-O-D-glucal 6 is 13% and 8%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bioactive molecules; carbohydrates; D-glucal; Ferrier rearrangement; Pyrones

Diastereoselective synthesis of beta-ether derivatives of artemisinin, an antimalarial drug: the effect of nitrile on stereoselectivity - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2016)
Malaria is a life-threatening disease affecting a major portion of the world's population with considerable loss of human life. Artemisinin, isolated from Artemisia annua, its oil- and water-soluble derivatives, and other known antimalarials are recommended for artemisinin combination therapy by the World Health Organization. We have established a method for the stereoselective synthesis of beta-ether derivatives of dihydroartemisinin in high yield and high diastereoselectivity. The reaction either in acetonitrile or dichloromethane/trichloroacetonitrile (6:1) mixtures at 0 degrees C or room temperature, respectively, furnished the antimalarial drugs artemether 3 or arteether 4 in high yield with a high diastereomeric ratio. The effect the nitrile has on the yield and stereoselectivity is mechanistically explained.
Keywords: antimalarials; arteethers; artemisinin; nitriles; trichloroacetimidates

Naturally occurring anti-TB agents: isolation, chemical transformations and in vitro antitubercular activities of secondary metabolites of rhizomes of alpinia galanga - Valkute, Tushar R.; Arkile, Manisha A.; Sarkar, Dhiman; Bhattacharya, Asish K. (Planta Medica International Open, 2016)
A bioactivity-guided chemical examination of the acetone extract of the rhizomes of Alpinia galanga led to the isolation of six sec-ondary metabolites, eucalyptol derivative (1)andphenylpropa-noids (2–6). The structures of all of the isolated compounds (1–6)wereelucidatedonthebasisoftheirspectraldata.Theisolatedcompounds (1–6)werein vitro assayed against active and dor-mant phenotypes of Mycobacterium tuberculosis H37Ra, respec-tively. Interestingly, 1′S-1′-acetoxychavicol acetate (2)showedgood antitubercular activities against both active and dormantphenotypes of M. tuberculosis with IC50 values of 1.04 µM and2.69 µM, respectively. Tsuji-Trost and homodimerization reac-tions of the active compound (2)respectivelyresultedinthefor-mation of two analogues, 7and 8.Bothofthesesynthesizedana-logues were also found to be active in vitro against active [IC50 sof3.24 and 3.87 µM, respectively, for compounds 7and 8]anddor-mant [IC50 sof8.33and2.41µM,respectively,forcompounds7and 8]phenotypesofM. tuberculosis H37Ra, respectively.

Biomimetic total synthesis of angiopterlactone B and other potential natural products - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic Letters, 2017)
A one-pot biomimetic synthesis of (-)-angiopterlactone B and its enantiomer (+)-angiopterlactone B has been accomplished via TBAF-catalyzed tandem ring contraction followed by oxa-Michael/Michael addition sequence. Comparison of specific optical rotations, absolute configurations, and CD spectra of natural, synthesized (-)-angiopterlactone B and (+)-angiopterlactone B unequivocally proves that the isolated angiopterlactone B must be levorotatory. Synthesis of hitherto undiscovered natural products 18 and 20 and analogues of angiopterlactone B demonstrate the versatility of this method.

Norepinephrine alkaloids as antiplasmodial agents: Synthesis of syncarpamide and insight into the structure-activity relationships of its analogues as antiplasmodial agents - Aratikatla, Eswar K.; Valkute, Tushar R.; Puri, Sunil K.; Srivastava, Kumkum; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2017)
Syncarpamide 1, a norepinephrine alkaloid isolated from the leaves of Zanthoxylum syncarpum (Rutaceae) exhibited promising antiplasmodial activities against Plasmodium falciparum with reported IC50 values of 2.04 mu M (D6 clone), 3.06 mu M (W2 clone) and observed by us 3.90 mu M (3D7 clone) and 2.56 mu M (K1 clone). In continuation of our work on naturally occurring antimalarial compounds, synthesis of syncarpamide 1 and its enantiomer, (R)-2 using Sharpless asymmetric dihydroxylation as a key step has been accomplished. In order to study structure-activity-relationship (SAR) in detail, a library of 55 compounds (3-57), which are analogues/homologues of syncarpamide 1 were synthesized by varying the substituents on the aromatic ring, by changing the stereocentre at the C-7 and/or by varying the acid groups in the ester and/or amide side chain based on the natural product lead molecule and further assayed in vitro against 3D7 and K1 strains of P. falciparum to evaluate their antiplasmodial activities. In order to study the effect of position of functional groups on antiplasmodial activity profile, a regioisomer (S)-58 of syncarpamide 1 was synthesized however, it turned out to be inactive against both the strains. Two compounds, (S)-41 and its enantiomer, (R)-42 having 3,4,5-trimethoxy cinnamoyl groups as side chains showed better antiplasmodial activity with IC50 values of 3.16, 2.28 mu M (3D7) and 1.78, 2.07 mu M (I(1), respectively than the natural product, syncarpamide 1. Three compounds (S)-13, (S)-17, (S)-21 exhibited antiplasmodial activities with IC50 values of 6.39, 6.82, 6.41 mu M against 3D7 strain, 4.27, 7.26, 2.71 mu M against K1 strain and with CC50 values of 147.72, 153.0, >200 mu M respectively. The in vitro antiplasmodial activity data of synthesized library suggests that the electron density and possibility of resonance in both the ester and amide side chains increases the antiplasmodial activity as compared to the parent natural product 1: The natural product syncarpamide 1 and four analogues/homologues out of the synthesized library of 55, (S)-41, (R)-42, (S)-55 and (S)-57 were assayed in vivo assay against chioroquine-resistant P. yoelii (N-67) strain of Plasmodium. However, none of the five molecules, 1, (S)-41, (R)-42, (S)-55 and (S)-57 exhibited any promising in vivo antimalarial activity against P. yoelii (N-67) strain. Compounds 4, 6, 7 and 11 showed high cytotoxicities with CC50 values of 5.87, 5.08, 6.44 and 14.04 mu M, respectively. Compound 6 was found to be the most cytotoxic as compared to the standard drug, podophyllotoxin whereas compounds 4 and 7 showed comparable cytotoxicities to podophyllotoxin. (C) 2017 Elsevier Masson SAS. All rights reserved.

Chemo-biological evaluation of antidiabetic activity of M entha arvensis L. and it's role in inhibition of advanced glycation end products - Agawane, Sachin B.; Gupta, Vidya S.; Kulkarni, Mahesh J.; Bhattacharya, Asish K.; Koratkar, Santosh (Journal of Ayurveda and integrative medicine, 2018)
Background: There has been enormous curiosity in the development of alternative plant based medicines to control diabetes, oxidative stress and related disorders. One of the therapeutic approaches is to reduce postprandial release of glucose in the blood. Two key enzymes that are involved in reducing postprandial glucose are α-amylase and α-glucosidase. Mentha arvensis L. has been traditionally used by several tribes as a medicinal plant to treat various disorders. Objective: The present study was undertaken to test M. arvenisis L. for inhibition of postprandial hyperglycemia. Material and method: We performed various in vitro and in vivo tests to evaluate efficacy of M. arvenisis L. for antidiabetic activity (postprandial hyperglycemia). Results: Methanolic extract of M. arvensis L. leaves showed DPPH free radical scavenging activity (more than 78% μg/μl) and high antiglycation potential (more than 90% inhibition of AGE formation). Methanolic extract also showed remarkable inhibitory effects on α-amylase (more than 50% μg/μl) and α-glucosidase (68% μg/μl) and significant inhibition of postprandial hyperglycemia in starch induced diabetic Wistar rats. Conclusion: The non-insulin dependent antidiabetic or inhibition of postprandial hyperglycemic activity of methanolic extract of M. arvensis L. leaves was shown by using in vitro and in vivo approaches in the present study.

Hydroxyl directed C-arylation: synthesis of 3-hydroxyflavones and 2-phenyl-3-hydroxy pyran-4-ones under transition-metal free conditions - Paula, Sayantan; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2018)
An efficient, transition-metal free and direct C-arylation of 3-hydroxychromone moieties in the presence of a base, air as an oxidant and arylhydrazines as arylating agents to furnish highly biologically active flavonols or 3-hydroxyflavones has been developed. We have further extended our methodology for the C-arylation of the 5-hydroxy pyran-4-one moiety. The role of the free hydroxyl group towards C-arylation has been delineated.

Hemiketal-keto tautomerism in 2-deoxy-delta-lactones mediated by 2-lithiothiazole in solution state: a formal synthesis of DAH, Kamusol and their C-5 Epimers - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2019)
The reactions of 2-lithiothiazole on 3,4,6-tri-O-benzyl-2-deoxyglyconolactones have been studied, which resulted in the formation of two products, major (3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal) and minor products 3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal hemiketal. The hemiketal-keto tautomerism in solution was observed in the minor product. The tautomerism has been studied in various organic solvents and their ratios have been determined by H-1 NMR spectroscopy. The major product from the reaction of 2-lithiothiazole with 2-deoxygluconolactone was utilized for the synthesis of 3-deoxy-D-arabino-2-heptulosonic acid DAH 4 a and 3-deoxy-D-arabino-2-heptulopyranose commonly known natural product kamusol 6 a via acid catalyzed hydration followed by stereoselective methyl glycoside bond formation. Similarly, major product from 2-deoxygalactonolactone furnished 5-epi-DAH 4 b (C-5 epimer of 4 a) and 5-epi-kamusol 6 b (C-5 epimer of 6 a). The minor product has also been utilized for the synthesis of DAH 4 a, 5-epi-DAH 4 b, kamusol 6 a and 5-epi-kamusol 6 b through a common intermediate, alpha-methyl glycosylated product.
Keywords: hemiketals; Ketones; tautomerism; thiazoles; umpolung

Synthesis of artemisinin derived glycoconjugates inspired by click chemistry - Goswami, Lakshmi; Paul, Sayantan; Kotammagari, Tharun K.; Bhattacharya, Asish K. (New Journal of Chemistry, 2019)
Herein we describe the synthesis of artemisinin based glycoconjugates (9a-i) through employing a Cu(i)-catalysed reaction between -propargylated dihydroartemisinin (7a) and azido sugars (8a-i), with moderate to excellent yields. Our synthesized artemisinin based glycoconjugates (9a-i) could prove to be an interesting class of bioactive molecules, suitable for the study of their various biological activities.

Unusual epimerization in styryllactones: synthesis of (-)-5-hydroxygoniothalamin, (-)-5-acetylgoniothalamin, and O-TBS-goniopypyrone - Kotammagari, Tharun K.; Paul, Sayantan; Bhattacharya, Asish K. (ACS Omega, 2019)
(-)-5-Hydroxygoniothalamin, (-)-5-acetylgoniothalamin, and (+)-5-hydroxygoniothalamin, isolated from the Goniothalamus genus, are synthesized from triacetyl-O-D-glucal by employing the Ferrier reaction, Mitsunobu reaction, and Jones oxidation as key steps. The synthetic procedure also yields the epimers of (-)-5-hydroxygoniothalamin and (+)-5-hydroxygoniothalamin employing acid-mediated transition-metal-free epimerization at C-5 of styryllactones. Further studies reveal that the epimerization is facilitated by the phenyl group present on the styryllactones. Also, depending on the dihydroxylation reaction conditions, various analogues of saturated styryllactones are synthesized utilizing oxa-Michael reaction conditions.

Enantioselective synthesis of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones and their application to the synthesis of novel highly potent antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (ACS Omega, 2020)
Racemic and enantioselective syntheses of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones have been achieved using Horner-Wadsworth-Emmons olefination of trityl protected alpha-phenyl-alpha-amino aldehydes with tetraethyl methylenediphosphonate and diethyl ((phenylsulfonyl)methyl)phosphonate, respectively, without any racemization. The present strategy has also been successfully applied to the synthesis of peptidyl vinyl phosphonate and peptidyl vinyl sulfone derivatives as potential cysteine protease inhibitors of Chagas disease, K11002, with 100% de. The developed synthetic protocol was further utilized to synthesize hybrid molecules consisting of artemisinin as an inhibitor of major cysteine protease falcipain-2 present in the food vacuole of the malarial parasite. The synthesized artemisinin-dipeptidyl vinyl sulfone hybrid compounds showed effective in vitro inhibition of falcipain-2 and potent parasiticidal efficacies against Plasmodium falciparum in nanomolar ranges. Overall, the developed synthetic protocol could be effectively utilized to design cysteine protease inhibitors not only as novel antimalarial compounds but also to be involved in other life-threatening diseases.

Short review of synthetic routes for the antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Organic Process Research & Development, 2020)
The disease epilepsy affects people of all ages and is due to a chronic neurological disorder in the brain. According to a report by the World Health Organization, epilepsy is one of the most common global neurological diseases. (R)-Lacosamide (Vimpat) was introduced by UCB Pharma in 2008 for the treatment of partial-onset seizures in patients suffering from epilepsy. This review summarizes all of the available synthetic strategies reported for (R)-lacosamide, which will help medicinal chemists in the further development of its synthesis.
Keywords: antiepileptic drug; epilepsy; lacosamide; serine derivative; synthesis

Synthesis of artemisinic acid derived glycoconjugates and their anticancer studies - Kotammagari, Tharun K.; Paul, Sayantan; Barik, Ganesh K.; Santra, Manas K.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2020)
Glycoconjugates, due to their diverse functions, are widely regarded as biologically important molecules. Artemisinic acid 1 occurs naturally in the plant Artemisia annua and is considered to be the biogenetic precursor of the antimalarial drug, artemisinin 2. We report herein the design and synthesis of diverse artemisinic acid derived glycoconjugates. We have synthesized 12-O-artemisinic acid-glycoconjugates (7a-k) and 12-N-artemisinic acid-glycoconjugates (8a-k) by utilizing Cu(i)-catalyzed azide-alkyne cycloaddition reactions (Click chemistry) with various synthesized sugar azides (6a-k) in good to excellent yields along with two fluorescently labeled compounds, 12-O-artemisinic acid-glycoconjugate 11 and 12-N-artemisinic acid-glycoconjugate 12, to investigate the mode of action of these compounds in biological systems. All the synthesized artemisinic acid glycoconjugates were assayed for their efficacy against the MCF7 cell line. Our anticancer studies indicated that all the synthesized compounds inhibited the growth of MCF7 cells in a dose dependent manner, barring compounds 4 and 7d. However, these compounds exhibit moderate cytotoxicity, as is evident from their IC50 values.

Combating multi-drug resistant malaria parasite by inhibiting falcipain-2 and heme-polymerization: Artemisinin-peptidyl vinyl phosphonate hybrid molecules as new antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Rana, Kalpeshkumar C.; Datta, Gaurav; Asad, Mohd; Sundararaman, Srividhya; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Artemisinin-based combination therapies (ACTs) have been able to reduce the clinical and pathological malaria cases in endemic areas around the globe. However, recent reports have shown a progressive decline in malaria parasite clearance in South-east Asia after ACT treatment, thus envisaging a need for new artemisinin (ART) derivatives and combinations. To address the emergence of drug resistance to current antimalarials, here we report the synthesis of artemisinin-peptidyl vinyl phosphonate hybrid molecules that show superior efficacy than artemisinin alone against chloroquine-resistant as well as multidrug-resistant Plasmodium falciparum strains with EC<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">50<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in pico-molar ranges. Further, the compounds effectively inhibited the survival of ring-stage parasite for laboratory-adapted artemisinin-resistant parasite lines as compared to artemisinin. These hybrid molecules showed complete parasite clearance in vivo using P. berghei mouse malaria model in comparison to artemisinin alone. Studies on the mode of action of hybrid molecules suggested that these artemisinin-peptidyl vinyl phosphonate hybrid molecules possessed dual activities: inhibited falcipain-2 (FP-2) activity, a P. falciparum cysteine protease involved in hemoglobin degradation, and also blocked the hemozoin formation in the food-vacuole, a step earlier shown to be blocked by artemisinin. Since these hybrid molecules blocked multiple steps of a pathway and showed synergistic efficacies, we believe that these lead compounds can be developed as effective antimalarials to prevent the spread of resistance to current antimalarials.

Design and synthesis of eugenol/isoeugenol glycoconjugates and other analogues as antifungal agents against Aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vermani, Maansi; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (RSC Medicinal Chemistry, 2022)
Glycoconjugates are biologically significant molecules as they tend to serve a wide range of intra- and extra-cellular processes depending on their size and complexity. The secondary metabolites of the plant Myristica fragrans, eugenol and isoeugenol, have shown antifungal activities (IC50 1900 mu M). Therefore, we envisioned that glycoconjugates based on these two scaffolds could prove to be potent antifungal agents. Triazole-containing compounds have shown prominent activities as antifungal agents. Based on this, we opined that a Cu(i) catalyzed click reaction could serve as the bridging tool between a eugenol/isoeugenol moiety and sugars to synthesize eugenol/isoeugenol based glycoconjugates. In our present work, we have coupled propargylated eugenol/isoeugenol and azido sugar to furnish eugenol/isoeugenol based glycoconjugates. In another approach, we have carried out hydroxylation of the double bond of eugenol and subsequent azidation of a primary alcohol followed by intramolecular coupling reactions leading to various other analogues. All the synthesized compounds were assayed against an opportunistic pathogenic fungus, Aspergillus fumigatus. Among the synthesized compounds, two analogues have exhibited significant antifungal activities with IC50 values of 5.42 and 9.39 mu M, respectively. The study suggested that these two analogues inhibit cell wall-associated melanin hydrophobicity along with the number of conidia. The synthesized compounds were found to be non-cytotoxic to an untransformed cell line.

Glycal mediated synthesis of piperidine alkaloids: fagomine, 4-epi-fagomine, 2-deoxynojirimycin, and an advanced intermediate, iminoglycal - Chand, Hemender R.; Tiwari, Mritunjay K.; Bhattacharya, Asish K. (RSC Advances, 2022)
Glucal and galactal are transformed into 2-deoxyglycolactams, which are important building blocks in the synthesis of biologically active piperidine alkaloids, fagomine and 4-epi-fagomine. In one of the strategies, reduction of 2-deoxyglycolactam-N-Boc carbonyl by lithium triethylborohydride (Super-Hydride (R)) has been exploited to generate lactamol whereas reduction followed by dehydration was utilized as the other strategy to functionalize the C-1-C-2 bond in the iminosugar substrate. The strategies provide the formal synthesis of 2-deoxynojirimycin, nojirimycin and nojirimycin B. DFT studies were carried out to determine the reason for the failure of the formation of the 2-deoxygalactonojirimycin derivative. Further, DFT studies suggest that phenyl moieties of protecting groups and lone pairs of oxygen in carbamate group plays a vital role in deciphering the conformational space of the reaction intermediates and transition-state structures through cation-pi or cation-lone pair interactions. The influence of these interactions is more pronounced at low temperature when the entropy factor is small.

Isoeugenol affects expression pattern of conidial hydrophobin gene RodA and transcriptional regulators MedA and SomA responsible for adherence and biofilm formation in Aspergillus fumigatus - Gupta, Lovely; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Archives of Microbiology, 2022)
Aspergillus fumigatus is one of the major pathogenic fungal species, causing life-threatening infections. Due to a limited spectrum of available antifungals, exploration of new drug targets as well as potential antifungal molecules has become pertinent. Rodlet layer plays an important role in adherence of fungal conidia to hydrophobic cell surfaces in host, which also leads to A. fumigatus biofilm formation, contributing factor to fungal pathogenicity. From decades, natural sources have been known for the development of new active molecules. The present study investigates effect of isoeugenol on genes responsible for hydrophobins (RodA), adhesion as well as biofilm formation (MedA and SomA) of A. fumigatus. Minimum inhibitory concentrations (MIC and IC50) of isoeugenol against A. fumigatus were determined using broth microdilution assay. The IC50 results showed reduced hydrophobicity and biofilm formation as well as eradication after treatment with the compound and electron micrograph data corroborated these findings. The qRT-PCR showed a significant downregulation of genes RodA, MedA, SomA and pksP involved in hydrophobicity and biofilm formation. SwissADME studies potentiated drug-like propensity for isoeugenol which formed four hydrogen bonds with low binding energy (- 4.54 kcal/mol) at the catalytic site of RodA protein studied via AutoDock4. Hence, the findings conclude that isoeugenol inhibits conidial hydrophobicity and biofilm formation of A. fumigatus and further investigations are warranted in this direction.
Keywords: Aspergillus fumigatus; Hydrophobicity; Isoeugenol; Transcription regulators; Virulence

Accelerated Rauhut-Currier dimerization enabled the synthesis of (+/-)-incarvilleatone and anticancer studies - Kotammagari, Tharun K.; Misra, Sweta; Paul, Sayantan; Kunte, Sunita; Gonnade, Rajesh G.; Santra, Manas K.; Bhattacharya, Asish K. (Beilstein Journal of Organic Chemistry, 2023)
The total synthesis of racemic incarvilleatone has been achieved by utilizing unexplored accelerated Rauhut-Currier (RC) dimeriza-tion. The other key steps of the synthesis are oxa-Michael and aldol reactions in a tandem sequence. Racemic incarvilleatone was separated by chiral HPLC and the configuration of each enantiomer was determined by single-crystal X-ray analysis. In addition, a one-pot synthesis of (+/-)-incarviditone has been achieved from rac-rengyolone by using KHMDS as a base. We have also assessed the anticancer activity of all the synthesized compounds in breast cancer cells nonetheless, they exhibited very limited growth suppression activity.
Keywords: dimerization; incarviditone; incarvilleatone; oxa-Michael; Rauhut-Currier

Design and synthesis of 1,3-diynes as potent antifungal agents against aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (ChemMedChem, 2023)
Eugenol and isoeugenol, secondary metabolites isolated from the plant Myristica fragrans have displayed antifungal activities against Aspergillus fumigatus (IC50 1900 mu M). Compounds having conjugated unsaturation have been of great use as antifungals i. e. amphotericin B, nystatin and terbinafine etc. Hence, in the present study, we have designed and synthesised 1,3-diynes by utilizing Glaser-Hay and Cadiot-Chodkiewicz coupling reactions to furnish possible antifungal agents. Synthesis of 1,6-diphenoxyhexa-2,4-diyne derivatives was achieved by Cu(I) catalysed coupling of propargylated eugenol, isoeugenol, guaiacol, vanillin and dihydrogenated eugenol or eugenol in good to excellent yields. All the synthesized compounds were evaluated against pathogenic fungus A. fumigatus. Among all the synthesized compounds, one of the compounds was found to be exhibiting promising antifungal activity with IC50 value of 7.75 mu M thereby suggesting that this type of scaffold could pave the way for developing new antifungal agents. The most active compound was found to be low cytotoxic when assayed against L-132 cancer cell line. Effect of the most active compound on ergosterol biosynthesis has also been studied. Also, the most active compound exhibited significant anti-biofilm activity although the concentration was found to be higher than its anti-fungal activity. Morphological changes in the biofilm were remarkable under confocal laser scanning microscopy.
Keywords: 1; 3-Diynes; Antifungal agents; Aspergillus fumigatus; Cadiot-Chodkiewicz; Glaser-Hay

1,6-Conjugate addition of in situ generated aryldiazenes to p-quinone methides - Mamale, Ajay G.; Paul, Sayantan; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2024)
Herein we report a transition-metal free, base-mediated 1,6-conjugate addition of aryldiazenes to para-quinone methides (p-QMs). Arylhydrazines were used for the in situ generation of aryldiazenes using a base-mediated protocol in the presence of air as the oxidant. The 1,6-conjugate addition of aryldiazenes to para-quinone methides via a radical mechanism is followed by an oxidative rearrangement to furnish the desired product, arylhydrazones. Interestingly, our synthetic protocol results in the formation of an aryldiazene radical, which undergoes 1,6-conjugate addition with p-QMs to furnish the arylhydrazones.

Methanesulfonic acid-catalyzed friedel-crafts alkylation: towards sustainable synthesis of arylalkanes from donor-acceptor cyclopropane ketones - Goswami, Lakshmi; Paul, Sayantan; Mamale, Ajay G.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2024)
We present herein Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane ketones. The presence of the 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules inspired us to pursue the direct synthesis of these structural frameworks. Utilizing methanesulfonic acid (MeSO3H) as a catalyst, we achieved a more environmentally friendly and high-yielding synthesis, owing to its cost-effectiveness, biodegradability, transition-metal and additives free conditions. Furthermore, we have successfully extended our developed methodology to thiophenols, resulting in the production of sulfur-based butan-1-one derivatives in good yields. The presence of 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules prompted us to develop a Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane. image
Keywords: donor-acceptor cyclopropane; Friedel-Crafts alkylation; methanesulfonic acid; Phenols; thiophenol

Short review on the synthetic routes for the antiepileptic drug (S)-levetiracetam - Paul, Sayantan; Bhattacharya, Asish K. (Organic Process Research and Development, 2024)
Epilepsy is a chronic disorder characterized by recurrent unpredictable seizures. Levetiracetam (Keppra) was introduced by UCB for the treatment of partial onset seizures in patients above 16 years of age diagnosed with epilepsy. This review reports synthetic strategies available for the synthesis of (S)-levetiracetam and will certainly aid the quest for the development of new routes for its synthesis.
Keywords: antiepileptic drug; butyrolactam; epilepsy; levetiracetam; synthesis

Strategies employing transition-metal free conditions for C-C bond formation in indoles - Ghodake, Balaji M.; Paul, Sayantan; Bhattacharya, Asish K. (ChemistrySelect, 2024)
Indole motifs are omnipresent in nature and can be found in many natural products as well as pharmaceuticals. It is for this reason synthetic transformations of indole have become a topic of interest for the organic and medicinal chemist community for decades. In this review, we have emphasized the functionalization of indoles via transition-metal-free approaches. This review touches on many aspects in different sub-sections, which gives a proposition of the tactics employed for the functionalization of indoles and an overview of the road ahead. In this review, essentially transition-metal-free conditions for C-C bond formation reactions in indoles has been explored. This review describes various approaches of functionalization at the C-2, C-3, C-4 and C-7 position of indoles which comprises arylation, alkenylation, acylation, formylation, alkylation, bisindolyl and cyclization strategies. Also, strategies incorporating N-alkylation/arylation has also been covered. image
Keywords: Alkylation; Arylation; formylation; Indole; transition-metal free

Unveiling the cell wall-targeting mechanisms and multifaceted virulence modulation by a eugenol glycoconjugate against aspergillus fumigatus: insights from in vitro and in ovo studies - Gupta, Lovely; Verma, Shalini; Goswami, Lakshmi; Kamboj, Himanshu; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Journal of Applied Macrobiology, 2024)
Aim The primary objective of this study was to elucidate the putative cell wall-associated targets of compound 6i, a glycoconjugate of eugenol, in Aspergillus fumigatus, while also evaluating its toxicity and assessing histopathologic alterations in the liver, heart, and kidney of compound 6i-treated embryos using an in ovo model.Method To achieve this aim, compound 6i was synthesized, and a series of biochemical assays were performed to determine its impact on the fungal cell wall. Additionally, quantitative real time-PCR and liquid chromatography-mass spectrometry/mass spectrometry analyses were conducted to investigate changes in gene and protein expression profiles associated with melanin biosynthesis, conidiation, siderophore production, transcriptional regulation of beta-glucan biosynthesis, and calcineurin activity in A. fumigatus.Results The experimental findings revealed that compound 6i exhibited notable antifungal activity against A. fumigatus by perturbing cell wall integrity, hindering ergosterol, glucan, and chitin biosynthesis, and inhibiting catalase production. Moreover, relative gene expression and proteomic analyses demonstrated that compound 6i exerted both downregulatory and upregulatory effects on several crucial genes and proteins involved in the aforementioned fungal processes. Furthermore, increased expression of oxidative stress-related proteins was observed in the presence of compound 6i. Notably, the glycoconjugate of eugenol did not elicit cytotoxicity in the liver, heart, and kidney of chick embryos.Conclusion The current investigation elucidated the multifaceted mechanisms by which compound 6i exerts its antifungal effects against A. fumigatus, primarily through targeting cell wall components and signaling pathways. These findings underscore the potential of the eugenol glycoconjugate as a promising antifungal candidate, warranting further exploration and development for combating A. fumigatus infections.
Keywords: Aspergillus fumigatus; cell wall integrity; Eugenol; Glycoconjugate; Transcription regulators; Virulence

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.

Comprehensive in vitro and in silico assessment of eugenol glycoconjugates against azole and amphotericin B resistant Rhizopus spp. - Sen, Pooja; Gupta, Lovely; Chauhan, Aastha; Goswami, Lakshmi; Bhattacharya, Asish K.; Sengupta, Abhishek; Vijayaraghavan, Pooja (Molecular Biology Reports, 2025)
Background Rhizopus spp. is a major cause of mucormycosis, a severe infectious disease with high morbidity and mortality. Treatment is challenging due to rising antifungal resistance. Glycosylation is a crucial technique for enhancing the properties of phenolic compounds like eugenol. The present study aims to examine the antifungal efficacy of eugenol glycoconjugates against azole and amphotericin B-resistant Rhizopus isolates. Methods and results Out of 50 soil samples, 12 isolates belonging to Mucorales were obtained, of which 7 were identified as Rhizopus spp. via 18S ITS sequencing. Antifungal susceptibility testing (AST) revealed that all Rhizopus isolates were resistant to amphotericin B (MIC > 1 mu g/mL). Most isolates also showed resistance towards posaconazole (MIC > 1 mu g/mL) and itraconazole (MIC > 2 mu g/mL). AST of eugenol glycoconjugate (coded 6g) showed efficacy against resistant Rhizopus isolates, with MIC values ranging from 6.25 mu g/mL to 25 mu g/mL. Flow cytometry confirmed its fungicidal activity, correlating with MIC data. Compound 6g significantly reduced conidial germination within 24 h and exhibited no cytotoxicity on A549 lung cancer cells. In-silico analysis revealed a negative binding affinity of compound 6g for the spore coat protein CotH3, which could be a potential antifungal target. Conclusion Compound 6g could be an potential antifungal molecule against resistant Rhizopus spp, which requires further studies.
Keywords: Antifungals; Eugenol; Glycoconjugates; Mucormycosis; Resistance; Virulence

Cyclopropane containing triterpenoids, cycloartenone, and cycloartenol: isolation, chemical transformations, and anticancer studies - Paul, Sayantan; Mandal, Kartik; Santra, Manas K.; Bhattacharya, Asish K. (ChemistrySelect, 2025)
Cycloartenone and cycloartenol, two plant-derived triterpenoids possessing cyclopropane ring were isolated from the latex of Artocarpus heterophyllus (jackfruit). Cycloartenol was chemically modified to synthesize dihydrocycloartenol via acetylation and deacetylation methodology followed by hydrogenation. Hydroxyl group present in the cycloartenol was also employed for the nitro benzoate formation. All the isolated and synthesized compounds were assayed against MCF7 breast cancer cell line for their anticancer properties.
Keywords: Anticancer studies; Artocarpus heterophyllus; Chemical transformations; Cycloartenol; Cycloartenone

Tf2O-Induced C(sp2)-N(sp2) bond formation: one-pot synthesis of N-heteroarene quaternary salts in nonbenzenoid skeleton of tropolone alkaloids under mild reaction conditions - Lohote, Mahendra V.; Bhattacharya, Asish K. (Organic Letters, 2025)
Naturally occurring protoalkaloids, such as colchicine and colchicoside, have significant medical applications and are used globally to treat a variety of diseases. We report herein a C(sp2)-N(sp2) bond formation protocol via a Tf2O (triflic anhydride)-assisted one-pot aromatic nucleophilic substitution (SNAr) reaction on various naturally occurring biologically active compounds such as colchicine, 3-demethyl colchicine, and 2-methoxy tropone under mild reaction conditions. Synthesis of bench-stable heterotropone quaternary salts was achieved by the reaction of tropolone alkaloids with diverse non-nucleophilic N-heterocycles. The developed methodology demonstrates wide substrate scope with good to very good yield. Our devised approach paves the way for future drug design efforts involving bioactive natural products with tropolone skeletons.

One-pot synthesis of N-arylated benzotriazoles and benzotriazinones via in situ diazotization and aryne trapping - Ghodake, Balaji M.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2026)
N-Arylated benzotriazoles and 1,2,3-benzotriazin-4-ones are important structural motifs in synthetic and medicinal chemistry, valued for their distinctive frameworks and functional versatility. We have developed an efficient, one-pot strategy for the synthesis of N-arylated benzotriazoles and benzotriazinones. The protocol involves in situ diazotization of o-phenylenediamine or 2-aminobenzamide using tert-butyl nitrite (tBuONO), followed by trapping of arynes generated in situ from 2-(trimethylsilyl)aryltriflates in the presence of CsF. The methodology exhibits broad functional-group tolerance and was successfully applied to 47 substrates, affording yields in the range of 60-85%. Furthermore, gram-scale synthesis highlights the operational simplicity and practical utility of this approach.